331 Effect of acute hypoxia on left ventricular twist assessed by speckle tracking imaging - Dedobbeleer, Chantal; Deboeck, Gael; Lamotte, Michel; Naeije, Robert; Unger, Philippe (Archives of Cardiovascular Diseases Supplements, 2011)
The impact of hypoxia on left ventricular (LV) myocardial contractility remains debated. Objectives: We hypothesized that acute hypoxia in healthy people increases LV twist as a consequence of the cardiovascular adaptation to stress (increased sympathetic nerve activity). Because hypoxia increases heart rate, we aimed to control for this change by studying the same subjects under atropine during normoxia. We studied 21 subjects (mean age: 27 ± 7 years) without medical history. Echocardiography was performed in normoxia and after 30 minutes of hypoxia (12% FiO 2). Short axis basal and apical views were analyzed using speckle tracking software. LV twist was defined as the net difference between the apical and basal rotation. The effect of atropine on LV twist was tested in the same subjects under normoxia. As expected, hypoxic breathing decreased arterial saturation in oxygen below 80% (table). Peak LV twist increased, as did heart rate, LV ejection fraction (LVEF) and systolic mitral annular velocity. Despite a decrease in mitral E/A ratio, early diastolic LV untwisting (at 5%, 10% and 15% of diastole) was not significantly modified under hypoxia. Atropine did not alter peak systolic twist (8.9 ± 3.1° versus 10.1 ± 2.6°, p = 0.09, without and with atropine, respectively), despite an increase in heart rate (from 64 ± 11 to 77 ± 11 beats/min, p = 0.0001). Acute hypoxia increases LV twist as well as other parameters of LV contractility. This change in LV twist does not result from the chronotropic effect of hypoxia. Values are means (SD) Normoxia Hypoxia p value SaO 2 (%) 97 (1.3) 76 (7.8) 0.0001 Heart rate (beats/min) 64 (11) 70 (9) 0.008 LVEF (%) 65 (5) 68 (7) 0.011 Systolic mitral annular velocity (cm/s) 8.0 (1.1) 8.7 (1.4) 0.03 E/A 2.1 (0.6) 1.8 (0.4) 0.015 Peak LV twist (° ) 8.9 (3.1) 11.1(2.8) 0.003